2017
DOI: 10.1111/scd.12251
|View full text |Cite
|
Sign up to set email alerts
|

Removable prosthesis hygiene in elders with Parkinson's disease

Abstract: Verbal instruction and positive reinforcement can improve prosthesis hygiene in elders with and without PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A combination of mechanical hygiene through brushing with chemical agents is a good choice for patients with dentures (24). Chemical agents with potential for bacterial growth inhibition are 1% sodium hypochlorite, vinegar and chlorhexidine digluconate and may be considered suitable products for cleaning dental prostheses (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of mechanical hygiene through brushing with chemical agents is a good choice for patients with dentures (24). Chemical agents with potential for bacterial growth inhibition are 1% sodium hypochlorite, vinegar and chlorhexidine digluconate and may be considered suitable products for cleaning dental prostheses (25).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical agents with potential for bacterial growth inhibition are 1% sodium hypochlorite, vinegar and chlorhexidine digluconate and may be considered suitable products for cleaning dental prostheses (25). Immersion in sodium hypochlorite for 10 minutes once a week does not appear to impair the acrylic alloys of a denture (24). The use of chemical agents might be a good strategy for denture cleansing to be performed by patient or a caregiver, as a part of an oral health program.…”
Section: Discussionmentioning
confidence: 99%
“…Although, authors Ribeiro, et al have observed, that patients with PD have had more biofilm accumulation on their prostheses, compared to non-PD patients. During their research, results were more apparent on the maxillary prosthesis [14]. Also, Fukoka, et al used video fluorography, which led them to…”
Section: Resultsmentioning
confidence: 99%
“…Patients report more discomfort (pain, dry mouth, denture issues) as well as chewing difficulties (related to either teeth, denture, or masticatory function) and dysphagia. They have a worse perception of their oral health [3,77], and a decreased oral health-related quality of life [4,48,52,69,71,72,78,79]. Of interest, changes in the oral microbiota are also reported, though the significance and extent of such alterations, as well as their link with PD remain to be determined (causal/correlative/consecutive) [74,[80][81][82].…”
Section: Oral Health Is Poorer In Pdmentioning
confidence: 99%
“…Decline in the quality of the toothbrushing (not necessarily in the frequency [74]) and lack of interdental cleaning reduce the efficacy of plaque control, promoting gingivitis, and initiating or aggravating periodontitis and dental caries. Moreover, such fine movement impairments induce more difficulties in the frequency and quality of prosthesis hygiene, leading to biofilm accumulation [78]. Discomfort with mouthwashes, possibly due to dysphagia and fear of choking, has also been reported [68].…”
Section: Problems Faced In Maintaining Good Oral Care At Homementioning
confidence: 99%